PERANCANGAN PEMBERSIH GAS BUANG KAPAL DENGAN KAPASITAS 70.000 KG/JAM - Anggi Anggara; Qomaratun Nurlaila (Fakultas Teknik, Universitas Riau Kepulauan, 2021)
Marine air pollution regulations require the use of low Sulfur fuels to reduce SOx gas. Scrubber offers lower operating costs by allowing the use of high-sulfur fuels that are cheaper for fuel, capital costs and operating costs as an alternative to low-sulfur fuels, such as Liquid Natural Gas (LNG). It is necessary to design a ship exhaust gas cleaner (Scrubber). In the IMO 2020 Rules and Marpol Annex VI there are no Scrubber design standards that regulate calculations, material selection, and others. However, IMO 2020 and Marpol require that the exhaust gas purifier produced by the scrubber released into the air must reach 97.5% 99.5% cleaning and the minimum water pH is 3 which can be determined using the OLIanalyzer Software. The components of the scrubber consist of shell, body flange, scrubber head, nozzle, lug support scrubber, Spray Nozzle, Distributor Pipe, Packing Bed Support, Packing Bed, Venturi Scrubber, Demister. From three times doing scrubber simulation using OLIanalyzer Software on the Delta Pioneer engine, 80% performance was produced and produced gas output of 160 ppm and water pH of 6.6 pH. So that the scrubber design can be applied to the pioneer delta ship engine with a capacity of 70,000 Kg/h.